"Banter, bollockings and beatings": The occupational socialisation process in Michelin-starred kitchen brigades in Great Britain and Ireland. Issue 3 (19th March 2018) - Giousmpasoglou, Charalampos; Marinakou, Evangelia; Cooper, John
Abstract : Purpose: This study aims to conceptualise how the occupational socialisation of young chefs is conducted in Michelin-starred restaurants in Great Britain and Ireland; the key role of banter and bullying in this process is explored and critically discussed. Design/methodology/approach: This qualitative research critically discusses the data from 54 in-depth, face-to-face interviews with male and female Michelin-starred chefs in Great Britain and Ireland. A flexible interview guide was used to ensure all key areas, and topics discussed earlier in the literature review were covered. The rich data from the interviews were categorised in four different themes. Findings: Drawing upon the fieldwork, fresh insights into the social structures, processes and group dynamics which underpin the socialisation process of young chefs are revealed in the participants' own words. Four areas emerged from the usage of thematic analysis: occupational status, discipline and hierarchy in kitchen brigades, gender segregation in kitchen brigades and the role of banter and bullying in occupational socialisation. Research limitations/implications: This study generates empirical data that inform contemporary debates about the role of banter and bullying in the occupational socialisation process of new members in Michelin-starred restaurants. A conceptual framework on the process of occupational socialisation in Michelin-starred kitchen brigades in Great Britain and Ireland is also provided. Practical implications: The findings of this study suggest that banter and bullying are deeply embedded in chefs' occupational culture; they also play a key role in the process of induction and occupational socialisation of the new recruits. In addition, gender segregation was found to be a persistent problem in commercial kitchens – young female chefs have to endure the same harsh conditions during the induction and occupational socialisation process. A recommended course of action to eradicate this phenomenon involves HR professionals, hospitality managers and the Michelin Guide. Originality/value: The understanding of chefs' induction and occupational socialisation is deemed crucial for successful hospitality operations; nevertheless, this still remains an under-researched area. This study is unique in terms of scale and depth; it is expected to provide useful insights in both theoretical and practical perspective, regarding the induction, socialisation and eventually, retention of young chefs in Michelin-starred restaurants.